Hubungan Intensitas Penggunaan Game Online dengan Tingkat Kecemasan pada Remaja SMAN 1 Wanadadi - Rindhy Mei Adzelina; Ita Apriliyani; Tri Sumarni (Jurnal Ilmu Kesehatan dan Gizi, 2026)
Online games are one of the digital entertainment activities widely favored by adolescents; however, high-intensity use can lead to psychological impacts, one of which is anxiety. Anxiety in adolescents is characterized by feelings of restlessness, irritability, difficulty concentrating, and sleep disturbances, especially when they are unable to play online games or when they experience defeat in the game. This study aimed to determine the relationship between the intensity of online game use and the level of anxiety among adolescents. This study used a quantitative design with a cross-sectional approach, involving 113 respondents selected using a cluster sampling technique. The research instruments used were the DASS questionnaire and an online game usage intensity questionnaire, and the data were analyzed using univariate and bivariate analysis. The respondents in this study were adolescents from SMAN 1 Wanadadi, most of whom were 16 years old (49.6%) and predominantly female (61.9%). The intensity of online game use was mostly in the moderate category (55.8%), while the level of anxiety was mostly in the mild category (89.0%). The results showed that most respondents had a moderate level of online game usage intensity and a mild level of anxiety. Bivariate analysis indicated that there was no significant relationship between the intensity of online game use and the level of anxiety among adolescents, with a p-value of 0.425 and a contingency coefficient value of 0.076. Therefore, it can be concluded that there is no relationship between the intensity of online game use and the level of anxiety among adolescents.